PENGEMBANGAN BAHAN AJAR BOOK CREATOR BERBANTU WEBSITE DIGITAL MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SD - Herlina Hasanah; Ratih Nor Aila; Nopriani Rahma Sari; Imrohatun; Muhammad Syabrina (Al-mujahidah, 2025)
This research aims to develop teaching materials based on the Book Creator application which is supported by the use of digital websites to increase students' understanding of cultural diversity in Indonesia. The method used in this research is Research and Development (R&D), which is a systematic approach designed to create new products or innovations. The analysis results from the questionnaire show that Book Creator-based teaching materials assisted by digital websites obtained the following average scores: 95.99% from material experts, 97.41% from design experts, 92.11% from teachers, and 89.27 % of student responses. After testing. The students' pretest results showed an average score of 47, while the average score on the posttest increased to 80, which shows an increase in student understanding by 33. Technology-based teaching materials that utilize Book Creator are designed to increase students' interest in learning, encourage their active participation, and maximize learning outcomes. Apart from that, other digital platforms, such as Canva, can also support the learning process. Canva is a bold design application that allows the creation of various works such as posters, graphics, brochures, presentations, logos, videos, and even book covers. Using Book Creator with the help of digital websites can be an effective alternative in encouraging students' enthusiasm for learning, so that their understanding of the material can increase significantly.